Pengaruh Organizational Justice, Job Insecurity dan Pengembangan Karir terhadap Turnover Intention: (Studi pada Karyawan Mood Studios di Jakarta Selatan) - Ratna Febriyani Safitri; Widi Wahyudi (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to determine whether there is an influence on Organizational justice (X1), Job insecurity (X2), and Career Development (X3) on Turnover intention at Mood Studios in South Jakarta. The research used in this study is quantitative, the sampling technique used is non probability. The sample used in this study were 53 respondents. The analysis technique used is descriptive analysis (primary data), the analytical tool used is multiple linear regression using SPSS v.22 software. The results of this study indicate the regression value equation, namely Y = 30.088 + (-0.22) X1 + 0.350 X2 + 0.306 X3 + € so it can be concluded that Organizational justice has no significant effect on Turnover intention, Job insecurity has no significant effect on Turnover intention, Career Development has a significant effect on Turnover intention. Contribution of the three independent variables R2 is 53.7% to Turnover intention (Y) and the remaining 46.3% is influenced by other factors.